Selective collection of bio-waste in a non-intensive urban region – Producers’ characterization - Brás, Isabel (2022)
The European circular economy targets and waste policies have gradually focused on bio-waste, which is considered one of several key waste streams and is urgently needed to develop strategies for their selective collection. In non-intensive urban regions, a selective collection is a challenge due to the dispersion of bio-waste producers. This work intended to characterize the bio-waste producers, in Planalto Beirão region (Portugal) and define strategies for their management. Planalto Beirão is a non-intensive urban region in the center of Portugal composed of 19 municipalities. The methodology involved collecting data from non-domestic bio-waste producers in Portuguese databases. The data of non-domestic producers were divided into 4 categories: HORECA sector (hotels, restaurants and coffee shops), Food commerce (wholesale and retail sale), Tea houses and Social services (education and activities in social support with and without accommodation). The analyzed data from the 4 categories of non-domestic bio-waste producers indicated that hotels, restaurants and coffee shops represented 46% of producers, followed by Food commerce, Social services and Tea houses with 33%, 17% and 4%, respectively. Viseu was determined as the municipality with the highest potential to implement a successful selective collection of bio-waste. In the Planalto Beirão region, the selective collection from non-domestic bio-waste producers must be done door-to-door, in higher-density areas. In rural areas, valorization should be introduced locally by the producers or the community.